Boundary conditions for the emergence of relational trust among exporters and importers. Issue 3 (15th November 2018) - Ceyhan, Semih; Dogan, Ismail Cagri; Yildiz, Mehmet; Barca, Mehmet
Abstract : Purpose: This study looks to the answer of whether importers and exporters can develop relational trust and minimize the monitoring and control costs used to prevent opportunistic behavior in a trust relationship. Despite increasing scholarly interest in calculative and relational trust, the boundary conditions affecting the transformation of calculative trust into relational trust remain unaddressed. In response, this study aims to investigate the boundary conditions for the emergence of relational trust in inter-organizational relationships between Chinese exporters and Turkish importers. Design/methodology/approach: Data were collected from Turkish SMEs that import from China. To measure trust between parties, semi-structured interviews with top managers and/or decision-making company owners were conducted. Interview questions covered three categories: antecedents of trust, ways of developing trust and outcomes of trust. Findings: Results indicated that inter-organizational relationships between Chinese and Turkish firms lack relational-based trust. Most trade transactions between two parties are based on calculations of profit/loss, and Turkish firms use intermediary mechanisms to overcome lack of trust in this environment. The most important boundary conditions for the emergence of relational trust are behavioral uncertainty, the opportunistic behavior of Chinese suppliers and language and cultural barriers. Originality/value: This study contributes to the existing literature by addressing the hitherto unaddressed question of what the boundary conditions are for the transformation of calculative trust into relational trust.